2019
DOI: 10.15171/apb.2019.035
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Pyruvic Acid Salt Against Lithium Toxicity and Oxidative Damage in Human Blood Mononuclear Cells

Abstract: Purpose: Aim of present work was to study cytoprotective properties of lithium pyruvate, as a prospective pharmacological agent. Pyruvate has a lot of potential benefits due to positive influence on cell metabolism. Lithium is "gold-standard" mood-stabilizer. Combination of both may lead advantages. Methods: Lithium pyruvate was tested as cytoprotector on human blood mononuclears under induced oxidative stress. Cells were obtained from healthy donors and patients with alcoholism. The detection of cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…In the biochemical industry, it can be used as a synthetic precursor for n -butanol, l -alanine, l -tyrosine, isobutanol, and so on. In the pharmaceutical industry, it can be used to synthesize isoniazid pyruvate, vitamin B, and 4-phenyl-2-oxobutyric acid ethyl ester and has antioxidant effects . In the agricultural field, it can be used to synthesize pesticides such as cycloprothrin .…”
Section: Synthesis and Application Of Pyruvatementioning
confidence: 99%
See 1 more Smart Citation
“…In the biochemical industry, it can be used as a synthetic precursor for n -butanol, l -alanine, l -tyrosine, isobutanol, and so on. In the pharmaceutical industry, it can be used to synthesize isoniazid pyruvate, vitamin B, and 4-phenyl-2-oxobutyric acid ethyl ester and has antioxidant effects . In the agricultural field, it can be used to synthesize pesticides such as cycloprothrin .…”
Section: Synthesis and Application Of Pyruvatementioning
confidence: 99%
“…In the pharmaceutical industry, it can be used to synthesize isoniazid pyruvate, 33 vitamin B, 34 and 4-phenyl-2oxobutyric acid ethyl ester 35 and has antioxidant effects. 36 In the agricultural field, it can be used to synthesize pesticides such as cycloprothrin. 37 In the food field, it is an important food additive and dietary supplement.…”
Section: ■ Synthesis and Application Of Pyruvatementioning
confidence: 99%
“…Numerous studies have reported that oxidative stress is the most important mechanism for lithium-induced damage [10][11][12]. In this context, several studies demonstrated the role of lithium-induced oxidative stress on testicular tissue and the semen of animals and humans [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…PA calcium salts were demonstrated to speed up fatty acid metabolism, while also helping to reduce serum cholesterol levels [6]. PA also possesses antioxidant effects and could be used as a nutraceutical to treat diabetes II [7,8].…”
Section: Introductionmentioning
confidence: 99%